A phase 3 randomized study evaluating sialic acid extended-release for GNE myopathy. (30th April 2019) - Lochmüller, Hanns; Behin, Anthony; Caraco, Yoseph; Lau, Heather; Mirabella, Massimiliano; Tournev, Ivailo; Tarnopolsky, Mark; Pogoryelova, Oksana; Woods, Catherine; Lai, Alexander; Shah, Jinay; Koutsoukos, Tony; et al.
Abstract : Objective: To investigate the efficacy and safety of aceneuramic acid extended-release (Ace-ER), a treatment intended to replace deficient sialic acid, in patients with GNE myopathy. Methods: UX001-CL301 was a phase 3, double-blind, placebo-controlled, randomized, international study evaluating the efficacy and safety of Ace-ER in patients with GNE myopathy. Participants who could walk ≥200 meters in a 6-minute walk test at screening were randomized 1:1, and stratified by sex, to receive Ace-ER 6 g/d or placebo for 48 weeks and assessed every 8 weeks. The primary endpoint was change in muscle strength over 48 weeks measured by upper extremity composite (UEC) score. Key secondary endpoints included change in lower extremity composite (LEC) score, knee extensor strength, and GNE myopathy–Functional Activity Scale (GNEM-FAS) mobility domain score. Safety assessments included adverse events (AEs), vital signs, and clinical laboratory results. Results: Eighty-nine patients were randomized (Ace-ER n = 45; placebo n = 44). Change from baseline to week 48 for UEC score between treatments did not differ (least square mean [LSM] Ace-ER −2.25 kg vs placebo −2.99 kg; LSM difference confidence interval [CI] 0.74 [−1.61 to 3.09]; p = 0.5387). At week 48, there was no significant difference between treatments for the change in key secondary endpoints: LEC LSM difference (CI) −1.49 (−5.83 to 2.86); knee extension strength −0.40 (−2.38 to 1.58); and GNEM-FAS mobility domain score −0.72 (−2.01 to 0.57). Gastrointestinal events were the most common AEs. Conclusions: Ace-ER was not superior to placebo in improving muscle strength and function in patients with GNE myopathy. Classification of evidence: This study provides Class I evidence that for patients with GNE myopathy, Ace-ER does not improve muscle strength compared to placebo.